Constituents of Flower of Glycosmis pentaphylla (Retz.) Correa - Sinhababu, A.; Thakur, S. (Asian Journal of Chemistry, 2010)
Phytochemical investigation of the flower of Glycosmis pentaphylla(Retz.) Correa revealed isolation and identification of some alkaloids and an amide. The alkaloids, viz., arborine, arborinine, skimmianine, glycorine and glycosmicine were for the first time being reported from the flower of this plant and identification of benzamide-2-methylamino recorded its second occurrence in the plant kingdom.